Experimental Study on Vortex Tube as Cooling of Machine Panel - Herman Budi Harja (JURNAL MECHANICAL, 2014)
Generally, The air conditioning in the panel of CNC machine always uses electric fan to avoid overheating in electrical components. The availability of compressed air on CNC machines infrastructure allows the utilization of inovation through the use of vortex tube as a cold air generator. Vortex tube is a mechanical device that can separate the flow of pressurized air into hot and cold air. The cold air can be used as a substitute for cooler fan. The experimental study was conducted to examine the corelation between the value ratio value with generated cold temperatures, as well as its application as cooling panel. Vortex tube testing was conducted at Polman Bandung, it was tested on machine panel of CNC lathe machine (CKE61130) with a volume panel of 0.26m.3 The result of study showed that the vortex tube with a ratio value of 0.44 generates the lowest cold temperature. Furthermore the experiment test showed that vortex tube can function properly and maintain the air temperature between 25 ° C to 35 ° C.